Moderasi Beragama: Pengaruh Pemahaman Moderasi Beragama Terhadap Persepsi dan Perilaku Toleransi Pada Siswa SMK - Ariga, Muhammad Safari (Inovasi: Jurnal Diklat Keagamaan, 2024)
Based on the heterogeneous condition of SMK Subur Insani students based on ethnicity and religion, all students are male, and there have been no cases of religious moderation. This study aims to examine: 1) the level of understanding of religious moderation among students; 2) the level of students' perception of tolerance; 3) the level of student tolerance behaviour; 4) the influence of students' understanding of religious moderation on students' perceptions of tolerance; and 5) the influence of students' understanding of religious moderation on students' tolerant behaviour at Subur Insani Sambas Vocational School. The research procedure used quantitative data; there were 66 respondents, but only 55 students filled out the questionnaire. Data was collected using an understanding of religious moderation questionnaire, a tolerance perception questionnaire, and a tolerance behaviour questionnaire. Data analysis uses descriptive and statistical analysis. The findings of this research are: 1) The level of understanding of students' religious moderation is very high n = 85.80%; 2) The level of perception of students' tolerance is very high n = 91.91%; 3) The level of student tolerance behavior is very high n = 91.10%; 4) Understanding religious moderation (X) has a positive and significant influence on the perception of tolerance variable (Y1) seen from the statistical test results obtained tcount > ttable, namely 8.467 > 1.67412; 5) Understanding religious moderation (X) has a positive and significant influence on the tolerance behavior variable (Y2) in students at Subur Insani Sambas Vocational School as seen from statistical tests showing tcount > ttable, namely 5.247 > 1.67412.